Simple fix: The potential of escape gaps in enhancing the capture performance of crab pots used in the fishery of blue swimming crab, Portunus pelagicus (Crustacea, Decapoda, Portunidae), in the Philippines - Rizalyn M. Picoy-Gonzales; Nathaniel C. Añasco; Joy C. Lizada; Kazuhiko Anraku; Harold M. Monteclaro (Acta Ichthyologica et Piscatoria)
This study investigated the capture performance of two types of Philippine crab pots, a dome-type (DCP) and a box-type (BCP) installed with a pair of laboratory-tested escape gaps with flap through actual fishing operations. A total of 30 units of DCP and 30 units of BCP, of which 15 were gapped and 15 were conventional, were deployed in each fishing trial. Over the sampling period, 12 fishing trials were conducted resulting in a total of 180 hauls per pot type per design. The results showed the potential of 48 × 25 mm escape gaps with flaps in improving the selectivity and efficiency of crab pot gears used in catching blue swimming crab Portunus pelagicus (Linnaeus, 1758). The gapped crab pots significantly reduced the catch of undersized P. pelagicus by 48% in DCP and by 79% in BCP. The non-target catch was also reduced in the gapped pots by 67% in DCP and 72% in BCP. In addition, the capture of legal-sized P. pelagicus was not affected by the presence of the escape gaps in both DCP and BCP. Further, catch species richness was reduced in gapped DCP. The catch retrieval and sorting time was also reduced in both gapped DCP and BCP.